Literary Culture in the Holy Roman Empire, 1555-1720 - Parente, James A. Jr; Erich Schade, Richard; Schoolfield, George C. (UNC Studies in the Germanic Languages and Literatures, 1991)
These essays discuss approaches to early modern literature in central Europe, focusing on four pivotal areas: connections between humanism and the new scientific thought the relationship of late sixteenth- and early seventeenth-century literature to ancient and Renaissance European traditions the social and political context of early modern writing and the poets' self-consciousness about their work. As a whole, the volume argues that early modern writing in central Europe should not be viewed solely as literature but as the textual product of specific social, political, educational, religious, and economic circumstances. The contributors are Judith P. Aikin, Barbara Becker-Cantarino, Thomas W. Best, Dieter Breuer, Barton W. Browning, Gerald Gillespie, Anthony Grafton, Gerhart Hoffmeister, Uwe-K. Ketelsen, Joseph Leighton, Ulrich Maché, Michael M. Metzger, James A. Parente, Jr., Richard Erich Schade, George C. Schoolfield, Peter Skrine, and Ferdinand van Ingen.